Analysis of Competency Development Policy for State Civil Apparatus (ASN) at Kotamobagu City Education and Training Personnel Agency - Sutrisno, Aditya Pratama; Dilapanga, Abdul Rahman; Wawointana, Thelma (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The purpose of this research is to describe and analyze managerial competency policies in supporting ASN career development in Kotamobagu City. This is to meet the competency needs of the apparatus in order to realize local government bureaucratic reform through a competency development policy strategy at the Kotamobagu City Education and Training Staffing Agency. This research method uses qualitative data and is described descriptively in the form of written or spoken words from people and observable behavior. Data collection techniques through direct observation and interviews with research subjects. The results showed that the level of education with indicators of structural training and leadership experience is dependent (has a strong relationship). This shows that the implementation of structural training (Pim 4 to Pim 1) and leadership experience (Echelon 4 - Echelon 1) has been carried out based on the classification of educational levels at the Kotamobagu City Education and Training Personnel Agency.